2014
DOI: 10.1016/j.ijdevneu.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of social context on endocrine function and Zif268 expression in response to an acute stressor in adolescent and adult rats

Abstract: There is a paucity of studies comparing social buffering in adolescents and adults, despite their marked differences in social behavior. We investigated whether greater effects of social buffering on plasma corticosterone concentrations and expression of Zif268 in neural regions after an acute stressor would be found in adolescent than adult rats. Samples were obtained before and after 1h of isolation stress and after either 1 or 3h of recovery back in the colony with either a familiar or unfamiliar cage partn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 73 publications
0
18
1
Order By: Relevance
“…For example, the contrast between negative effects of paired-housing on ethanol-exposed and control rats in the present study and some positive effects of housing ethanol-exposed rats in triads with two control animals observed by Middleton et al [51] suggests that the number of cage-mates may be a critical factor that should be explored in future studies. A number of studies have demonstrated that the presence of other rats can have a positive influence on physiological and behavioral responses to distress—a behavioral phenomenon known as social buffering [28, 32, 33, 56, 68, 69]. The present data suggest that adult PAE male rats do not benefit from social housing, however, whether PAE negatively impacts social buffering early in development and/or whether these acute manipulations of the social environment persist into adulthood has not been examined.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the contrast between negative effects of paired-housing on ethanol-exposed and control rats in the present study and some positive effects of housing ethanol-exposed rats in triads with two control animals observed by Middleton et al [51] suggests that the number of cage-mates may be a critical factor that should be explored in future studies. A number of studies have demonstrated that the presence of other rats can have a positive influence on physiological and behavioral responses to distress—a behavioral phenomenon known as social buffering [28, 32, 33, 56, 68, 69]. The present data suggest that adult PAE male rats do not benefit from social housing, however, whether PAE negatively impacts social buffering early in development and/or whether these acute manipulations of the social environment persist into adulthood has not been examined.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, brief exposures to a novel environment (Goldman et al, 1973) or social isolation (Hodges et al, 2014) result in similar corticosterone responses in pre-, mid- and post-adolescent rats. Furthermore, some stressors, such as exposure to lipopolysaccharide (Girard-Joyal et al, 2015; Goble et al, 2011) or placement in the open arm of an elevated plus maze (McCormick et al, 2008) evoke lesser ACTH and/or corticosterone secretion in pre- and mid-adolescent male rats and female mice compared to adults (Figure 3).…”
Section: Adolescent Development Of Hpa Stress Reactivitymentioning
confidence: 99%
“…Terranova, Cirulli, & Laviola, 1999;Varlinskaya, 2013) the stressor and those that focus on stress alleviation through social housing prior to and/or following (e.g. Hodges, Green, Simone, & McCormick, 2014;McCormick, Merrick, Secen, & Helmreich, 2007) the stressor (Kiyokawa, Takeuchi, & Mori, 2007). The vast majority of social-buffering studies have focused on mammals and many parameters have been used to measure social buffering.…”
mentioning
confidence: 99%
“…These include traditional stress indicators such as activation of the hypothalamic-pituitary-adrenal axis (e.g. increased heart rate, cortisol; Hodges et al, 2014) and behavioural responses (e.g. escape attempts, Gonzalez et al, 2013), through to neural responses (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation